2022
DOI: 10.3390/jof8050505
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis from Tissue: Histology and Identification

Abstract: The diagnosis and initiation of appropriate treatment against invasive fungal infections depend upon accurate identification of pathogens by pathologists and clinical microbiologists. Histopathology is often critical in providing diagnostic insight in patients with suspected fungal infections, and such findings are incorporated into the definitions of proven or probable disease caused by certain pathogens. Such examinations can offer provisional identifications of fungal organisms, which can help guide initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…11 Histological identification of fungi can be problematic due to overlapping morphological features and challenges in accurately assessing morphology in 2-dimensional tissue sections. 27 Structures convincingly resembling conidiophores were never seen within tissue sections to allow more specific histological identification of fungus-like organisms. Consistent with the histological findings, microbiological and molecular techniques identified several different fungi associated with these lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Histological identification of fungi can be problematic due to overlapping morphological features and challenges in accurately assessing morphology in 2-dimensional tissue sections. 27 Structures convincingly resembling conidiophores were never seen within tissue sections to allow more specific histological identification of fungus-like organisms. Consistent with the histological findings, microbiological and molecular techniques identified several different fungi associated with these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal cultures are considered the complementary gold standard tool for laboratory diagnosis, 11,27 but can be time consuming and technically challenging. As demonstrated by our study, a major challenge for marine mycology is the inability to easily culture the microbially diverse fungal populations, with plating methods favoring the isolation of faster growing generalist and osmotolerant genera, and many fungi not sporulating in culture, making visual identification challenging.…”
Section: Discussionmentioning
confidence: 99%
“…These moulds can disseminate via the bloodstream and can cause skin lesions ( 20 ). It is not possible to distinguish the species by microscopic appearance in tissue ( 19 , 31 ) ( Table 4 ). As there can be important differences in the treatment of infections caused by different species histology reports generally describe the type of fungal structures seen, for example, hyalohyphomycosis, rather than suggesting a causative organism ( 19 , 31 ).…”
Section: Systemic Fungal Infections That Can Disseminate To the Skinmentioning
confidence: 99%
“…Within tissue, hyphae may be: (i) hyaline septate, e.g., Aspergillus, Fusarium species; (ii) broad ribbon-like with rare septation which includes members of the order Mucorales; and (iii) pigmented or dematiceous, e.g., Cladophialophora, Exophiala, spp. [7]. However, the diagnostic accuracy of identification to genus or species level is less than 80% [8,9].…”
Section: Direct Examination and Histopathologymentioning
confidence: 99%
“…Either broad-range (or panfungal) assays for capturing "all fungi" or assays tailored to detect a specific genus/species may be used to directly detect fungal DNA in clinical specimens [2]. Panfungal PCR followed by DNA sequencing allows for the identification of the pathogen from a diverse range of clinical specimens, including formalin fixed paraffin embedded (FFPE) tissue, although the examination of the latter is only recommended where fungal forms are seen on histopathology [2,7,11]. One study reported results for blood, cerebrospinal fluid (CSF), and aspirates where the sensitivity, specificity, negative predictive value (NPV), and positive predictive value (PPV) were 100, 96, 100, and 86%, respectively.…”
Section: Nucleic Acid Detectionmentioning
confidence: 99%